POTENSI DAN PEMANFAATAN JASA LINGKUNGAN KAWASAN KARST GUA GUDAWANG - Joko Mijiarto; Tutut Sunarminto; Rachmad Hermawan (Department of Forest Resources Conservation and Ecotourism - IPB University, 2014)
Gudawang Cave Karst Area is one of the karst area that are located in Bogor. This karst area has the ecosystem service potential that aren’t maximally utilized. This happen because there's no information about what ecosystem service that owned by the manager. This condition leading to the need for identification ofecosystem service potential and its utilization by local community. Research was done at March to June 2013 through field observation, interview, and literature study. The result of this research indicated that from 10 identified cave all of them were natural habitat of wildlife as shown by 19 wildlife species that were discovered inside the cave. All of them were also potentialfor tourism because of the different characteristic in each caveidentified. As many as 8 from them are potential for carbon dioxide absorptionand water supply. Only 3 of all the identified cave that have beenmanaged as tourism object and only 1 of all the identified cave has been used as water supply for local community. Keywords : Ecosystem service potential, Gudawang Cave, Identification, Karst area, Utilization